Cluster teaching as an arena for continuing teacher professional development : a case study. - Phiri, Rachel Memory Mnyamula (My University, 2012)
Internationally, governments have recognized the significance of continuing teacher professional development in their attempts to reform their educational systems. However, not many have the resources and capacity to support teachers in this endeavor (Nelson & Slavit, 2008). Teachers‟ initiatives at their own professional development therefore become important steps towards realizing the goal of continuing teacher professional development and reforming the education sector. Using a case study approach, the study aimed to explore the use of cluster teaching as a form of teacher professional development in one cluster in Mpumalanga. It focuses on teachers‟ experiences of cluster teaching. Interviews and observations provided most of the data for this case study and analysis was ongoing during the data collection process. The views of participants and what I observed is presented before the analysis and interpretation is done. The argument developed in this study is that every form of teacher professional development is best suited for a particular purpose with particular kinds of teachers and hence, the need for as many forms as possible to meet the different purposes that PD has. Cluster teaching as a form of PD serves the purposes of helping teachers improve on their subject content and pedagogical knowledge and to have a positive impact on their attitudes and culture while at the same time helping to improve the performance of learners. When teacher-initiated, it acts as an effective form of teacher professional development and accountability and covers up for the lack of district support and poor resources in some schools. Such cluster teaching therefore becomes a productive way of improving teachers‟ professional practices in their own contexts.
Keywords: Cluster teaching; Continuing teacher professional development